Changes in Chemical Composition and Rice Cooking Quality Through the Utilization of Respiration Heat of Freshly Harvested Rice During Storage - Tanwirul Millati; Arief Rahmad Maulana Akbar; Susi Susi; Alia Rahmi (Center for Journal Management and Publication, 2017)
This study aims to determine the effect of the type of packaging and storage time on the chemical composition and rice cooking quality by utilizing the respiration generated heat of freshly harvested rice. â€œSiam Pandakâ€ variety of freshly harvested rice stored in black plastic bag and tarpaulin with storage time of 0, 1, 2, 3, 4 and 5 days. The results showed that the accumulation of respiration heat of freshly harvested rice during storage is only capable of raising the temperature in the packaging up to 28 â€“ 31Â°C, slightly higher than room temperature ranging between 26 â€“ 29Â°C. Types of packaging and storage time could increase water absorption capacity, protein and fiber contents; and reduce fat and carbohydrate contents. The increase in water absorption capacity was obtained in black plastic bag with storage time of one day, which amounted to 298.27% (an increase of 27.74% compared to control), the highest protein content with storage time of two days with a protein content of 8.56% (an increase of 7.31% compared to control), fiber content in the tarp packaging with storage time of five days, which amounted to 2.40% (an increase of 96.46% compared to control).